Improvement of Oil Flow Calculations in in Analytical Predictive Models of Thermal Recovery (Chemical Engineering Research Bulletin, 2008)
Cyclic Steam Stimulation (CSS) is the preferred thermal oil recovery method used allover the world. The extensive use of CSS by the oil industry points to the need for a simple performance prediction technique. Analytical models are capable of rough production estimates for various operating conditions. The most important aspect of flow calculation in thermal recovery is the proper evaluation of the oil viscosity. So far, in the analytical models, there has not been any attempt to calculate an average viscosity based on its aerial distribution. In case of heavy oil, it is also very important to include the conduction heat loss from the hot steam zone to the cold zone along with the convection heat loss. An improved average temperature calculation technique and a new method of evaluating the effect of spatial oil viscosity distribution have been presented in this study. Results are analyzed and discussed for the improved situation.Chemical Engineering Research Bulletin 11 (2007) 31-50